2012
DOI: 10.1126/science.1226338
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanoparticles: Cost Versus Benefit of Adding Targeting and Imaging Capabilities

Abstract: Nanoparticle-based drug delivery systems have been developed to improve the efficacy and reduce the systemic toxicity of a wide range of drugs. While clinically-approved nanoparticles have consistently shown value in reducing drug toxicity, their use has not always translated into improved clinical outcomes. This has led to the development of “multifunctional” nanoparticles, where additional capabilities like targeting and image contrast enhancement are added to the nanoparticles. However, additional functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
921
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,197 publications
(928 citation statements)
references
References 88 publications
3
921
1
3
Order By: Relevance
“…A few of these nanoparticles also contain targeting ligands (8,9) that aid in their internalization into tumor cells. Some of the issues with the use of targeting ligands such as added cost and complexity have recently been described (10). These designed, multifunctional nanoparticles are revealing interesting behaviors in early clinical trials, e.g., they can significantly reduce side effects of the therapeutic molecules they carry, and they do not show new side effects as a result of the nanoparticle.…”
mentioning
confidence: 99%
“…A few of these nanoparticles also contain targeting ligands (8,9) that aid in their internalization into tumor cells. Some of the issues with the use of targeting ligands such as added cost and complexity have recently been described (10). These designed, multifunctional nanoparticles are revealing interesting behaviors in early clinical trials, e.g., they can significantly reduce side effects of the therapeutic molecules they carry, and they do not show new side effects as a result of the nanoparticle.…”
mentioning
confidence: 99%
“…and have succeeded in enhancing the efficacy of DDS. Some nanoparticles using active targeting strategy have proceeded to phase I/II clinical trials and have shown positive results [4]. The active targeting strategy can increase the accumulation of drugs in the desired tissue and reduce side effects.…”
Section: Benefits Of Active Targeting On Drug Delivery System (Dds)mentioning
confidence: 99%
“…Each of these functionalities could bring further complexity to the design [11]. Here, we focus on the trade-off between achieving such multifunctional "magic bullets" and specificity at the nanoscale in the effort to improve early stage detection and reduce collateral damage as side effects, central issues in the field of nanotechnology in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%